STRUKTUR MIKROSKOPIS HATI TIKUS PUTIH (Rattus novergicus) AKIBAT PEMBERIAN EKSTRAK TANAMAN Tristaniopsis whiteana Griff. - Rahmawati Januar; Yusfiati '; Fitmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pelawan plant (Tristaniopsis whiteana Griff.) is used by people for blood cleaner after postpartum. Scientifically, pelawan is proven as antiurolithiasis agent. However, its secondary metabolite toxicity is still unknown. This study aimed to know the histological structure of liver tissue of white rat after being given pelawan extract. This study use 8 white rats that were divided into four groups. Control group was given food and water, P1 was given food and inducer solution (mixture from ethylene glycol and ammonium chloride), P2 group was given ethanol extract of pelawan leaves with inducer solution, and P3 group was given ethanol extract of pelawan leaves. Histological slides of white rat liver were made using paraffin method, stained with Hematoxylin-Eosin (HE). Result showed that the liver of white rat changed. Therefore, the treatment of inducer solution and ethanol extract of pelawan leaves was toxic because it changed the histopatologycal part.